2020
DOI: 10.1186/s13244-020-00857-8
|View full text |Cite
|
Sign up to set email alerts
|

Cortical ischaemic patterns in term partial-prolonged hypoxic-ischaemic injury—the inter-arterial watershed demonstrated through atrophy, ulegyria and signal change on delayed MRI scans in children with cerebral palsy

Abstract: The inter-arterial watershed zone in neonates is a geographic area without discernible anatomic boundaries and difficult to demarcate and usually not featured in atlases. Schematics currently used to depict the areas are not based on any prior anatomic mapping, compared to adults. Magnetic resonance imaging (MRI) of neonates in the acute to subacute phase with suspected hypoxic-ischaemic injury (HII) can demonstrate signal abnormality and restricted diffusion in the cortical and subcortical parenchyma of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Damage to the parasagittal cortex in term infants after HI is highly associated with poor neurodevelopmental outcomes including cognitive and learning deficits and epilepsy [28][29][30][31]. In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations.…”
Section: Discussionsupporting
confidence: 45%
“…Damage to the parasagittal cortex in term infants after HI is highly associated with poor neurodevelopmental outcomes including cognitive and learning deficits and epilepsy [28][29][30][31]. In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations.…”
Section: Discussionsupporting
confidence: 45%
“…These parasagittal injuries are described at the overlapping and contiguous watershed zones between named vascular territories including the anterior watershed (between the anterior and middle cerebral artery territories), the perisylvian watershed and the posterior watershed (between the posterior and middle cerebral artery territories). 24 We have however found that injury to the parasagittal cortex (of predominantly the frontal and parietal lobes) may also be because of severe acute profound HIBI. In API parasagittal injuries, there is involvement of the perirolandic cortex as well as the paracentral lobule and the subsequent Wallerian degeneration, which leads to subsidence of the parasagittal mantle.…”
Section: Partial Prolonged Ischemiamentioning
confidence: 82%
“… 14 This results in sparing of these high metabolic areas at the expense of the watershed areas of the cerebral hemispheres between the major arterial territories, especially at the borders between perfused zones, shown in Figure 13 . For term neonates, the external or cortical watershed area is more peripherally positioned at the grey–white matter interface between the major branches of the anterior and posterior circulation 24 (see Figure 14 ). The internal watershed or boundary zones are at the parasagittal subcortical white matter secondary to the cerebral arterial tree arrangement with the junction of the ventriculofugal vessels coursing outward from the ventricles and ventriculopetal vessels coursing inward from the cortex (see Figure 15 ).…”
Section: Partial Prolonged Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…In severe cases the whole cortex may be involved, while with milder injury, the principal areas damaged are the interfaces between the perfusion zones of the anterior, middle and posterior cerebral arteries. An excellent schematic derived from a medicolegal database of MR images of term neonates with partial-prolonged HI injury illustrates the geography of the inter-arterial watershed zone [89].…”
Section: Adjuncts To Comprehensive Carementioning
confidence: 99%